Exploring Skin Longevity Pathways: Rosa hybrid Extract-Mediated AMP-Activated Protein Kinase Activation, Antioxidant, and Autophagic Mechanisms in Human Keratinocytes - Olivier Gouin; Andrea Cavagnino; Gayané Azadiguian; Sibylle Jäger; Gilles Comte; Mohammed Bendahmane; Lionel Breton; Martin A. Baraibar; Annie F. Black (Cosmetics)
The skin is continuously exposed to environmental changes, rendering it vulnerable to damage from external stressors that contribute to premature skin aging. This study aims to explore skin longevity pathways stimulated by a rose extract (RE) derived from petals. Human keratinocytes treated with RE exhibited a significant increase in NRF2 (NF-E2-related factor 2; ≈2–4% of induction) and LAMP2A (Lysosome-Associated Membrane Protein 2A; ≈6–12% of induction) levels. The presence of RE significantly mitigated the increase in carbonylation levels (≈34–37% of protection) and the number of labeled P16INK4A cells (≈60–72% of protection), associated with proliferation arrest, both induced by exposure to BAP (Benzo[a]pyrene) coupled with UV-A (Ultraviolet A) irradiation. The beneficial effects mediated by RE were inhibited by Compound C, a specific AMPK inhibitor (AMP-activated protein kinase). The involvement of the AMPK pathway in mediating the beneficial effects of RE has been confirmed by assessing its activation through the evaluation of its phosphorylation state which was significantly elevated in the presence of RE compared to the stress condition. In conclusion, the activation of the AMPK pathway enhances antioxidant defenses and promotes autophagy. This dual action, mediated by RE, helps protect skin cells from oxidative damage and senescence while maintaining proteostasis, skin integrity, and cellular proliferation under pollution-induced stress (BAP + UV-A). These findings highlight the potential in mitigating age-related skin changes through the modulation of longevity pathways.